Combined heat and power from hydrothermal geothermal resources in Germany: An assessment of the potential. (March 2020) - Eyerer, S.; Schifflechner, C.; Hofbauer, S.; Bauer, W.; Wieland, C.; Spliethoff, H.
Abstract: This study investigates the potential of hydrothermal geothermal energy for combined heat and power (CHP) generation in Germany. Based on the theoretical potential of hydrothermal heat in place, the technical and economic potential is determined with a review and an analysis of existing geothermal plants. To this end, the thermodynamic and economic performance of operating power plants is analyzed and models for the efficiency and the production costs are developed. Based on this analysis, a technical potential of 12.2 PWh el and 16.7 PWh th as well as an economic potential of 9.1 PWh el and 12.5 PWh th is determined. In order to derive an annual contribution from the economic potential, the regeneration of the resource is taken into account. Considering a sustainable exploitation rate, an annual economic potential of 9.1 TWh el /a and 12.5 TWh th /a is derived. This corresponds to a share of 1.51% of the gross electricity demand and a share of 1.48% of the demand for space heating and domestic hot water. This analysis provides a profound review about the existing geothermal power plants and their thermodynamic and economic performance. Furthermore, the assessment of the geothermal potential in Germany is necessary for political decision making, particular with a view towards future adjustments of the feed-in tariffs defined by the Renewable Energy Act. Graphical abstract: Highlights: Potential analysis of combined heat and power generation from hydrothermal resources. The total economic potential of geothermal CHP in Germany is 9.1 PWh el and 12.5 PWh th . Renewable geothermal CHP can contribute to 1.51% of gross electricity demand. Renewable geothermal CHP can contribute to 1 .48% of low temperature heating demand.